ANALISIS PENGALAMAN BELAJAR SISWA DALAM MENGGUNAKAN MEDIA PEMBELAJARAN DIGITAL PADA SISWA MI MAARIF 01 TLOGOPUCANG - Dian, Lala; Muna Erawari; Feri Kristanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social communication and mastery of information through digital media have become essential in modern education, yet implementing these tools at the primary school level in rural areas presents unique challenges. This study aims to explore students' learning experiences in using digital media, analyze the challenges encountered, and identify coping strategies at MI Ma'arif 01 Tlogopucang. A descriptive qualitative method with a combined phenomenological and case study approach was employed. Data were gathered through non-participant observations, semi-structured interviews with 10 students, and documentation. The results indicate that digital media significantly enhances students' engagement and comprehension of materials through interactive content like educational videos and quizzes, which foster autonomous learning. Furthermore, digital platforms lower communication barriers between students and teachers. However, students face significant obstacles, including technical issues such as unstable internet connections in rural areas and psychological factors like decreased self-discipline due to distractions in the home environment. Students cope with these challenges by seeking alternative signal locations and utilizing the repeat features of digital applications. In conclusion, while digital media effectively enriches the learning experience at the Madrasah Ibtidaiyah level, its success heavily depends on infrastructure stability and parental guidance to maintain learning focus. Keywords: Digital Media, Learning Experience, Madrasah Ibtidaiyah.